Smart Amp System Using I2S - Lee, Ye Won; Kim, Young Jin (Journal of Korean Institute of Communications and Information Sciences, 2020)
A conventional wireless speaker delivers the sound source of a PC or a smartphone to its micro-controller unit (MCU) using bluetooth communication, and it outputs a sound source through a digital to analog converter (DAC) to an amplifier. At this time, analog errors may occur while processing data in real time in audio, and there are problems such as loss of sound source, noise addition, and sound quality degradation in the process of converting a digital signal to an analog signal. In this paper, unlike a conventional wireless speaker using a DAC, we propose a system that reduces sound loss and noise, improves power consumption and output by using I2S (Integrated Interchip Sound) communication and a smart amplifier.
Keywords: Bluetooth; I2S; Smart Amp